2009
DOI: 10.1053/j.semperi.2008.10.008
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Mechanisms of Nonimmune Thrombocytopenia in Neonates

Abstract: Thrombocytopenia affects up to 35% of all patients admitted to the neonatal intensive care unit (NICU). The causes of thrombocytopenia in neonates are very diverse, and include immune and nonimmune disorders. Most cases of thrombocytopenia encountered in the NICU are non-immune, and these will constitute the focus of this review. Specifically, we will first discuss the biological differences between neonatal and adult megakaryocytopoiesis, which contribute to explain the vulnerability of neonates to develop th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 74 publications
0
49
1
3
Order By: Relevance
“…6,7 It is believed that developmental differences between neonatal and adult MKs contribute to this vulnerability. 8 Specifically, neonatal MK progenitors possess a high proliferative potential and give rise to MKs smaller and of low ploidy that generate fewer platelets compared with adult MKs. The regulatory mechanisms underlying these developmental differences are unknown, but we have revealed a critical role of small non-coding RNAs (miRNAs) in the regulation of MK development.…”
Section: Microrna-9 Promotes Cell Proliferation By Regulating Runx1 Ementioning
confidence: 99%
“…6,7 It is believed that developmental differences between neonatal and adult MKs contribute to this vulnerability. 8 Specifically, neonatal MK progenitors possess a high proliferative potential and give rise to MKs smaller and of low ploidy that generate fewer platelets compared with adult MKs. The regulatory mechanisms underlying these developmental differences are unknown, but we have revealed a critical role of small non-coding RNAs (miRNAs) in the regulation of MK development.…”
Section: Microrna-9 Promotes Cell Proliferation By Regulating Runx1 Ementioning
confidence: 99%
“…The implemented study showed that out of 136 newborn who had thrombocytopenia, 34.6% mothers went through some type of complication during labor, such as: narrower pelvis, intrauterine infection, bleeding in the third stage of labor and so on. Placental insufficiency as risk factor for development of thrombocytopenia in the newborn in our study was found in 32.4% examinees, while some authors reduce the risk of thrombocytopenia development due to placental insufficiency to 1% [11]. In neonatological literature the above is explained by the fact that hypoxia in the newborn triggers abundant erythropoesis, which reduces the amount of progenitor cells needed for differentiation of megakaryocytes into thrombocytes [12].…”
Section: Discussionmentioning
confidence: 99%
“…12 Kadar TPO meningkat secara bermakna pada hari ke 4-5, dan tidak didapatkan perbedaan yang bermakna antara jumlah trombosit, TPO dan progenitor megakariosit pada bayi prematur. 31 Penelitian kami merupakan penelitian pertama yang membandingkan antara TPO dengan profil hematologi. Berdasarkan hasil analisis dengan ROC didapatkan area under curve (AUC) 51,3% dan nilai cut off TPO 259 pg/mL, dengan nilai sensitivitas 77,4%, spesifisitas 24,4%, NDP 63,6%, dan NDN 76,5%.…”
Section: Pembahasanunclassified